Analysis of the Level of Development of Social Competence of the Students of Pedagogical College - Natalya Borbych (Pedagogical Discourse, 2012)
This article deals with some scientific approaches to the definition of «social competence». The importance of social competence as the leading characteristic of the process of socialization is analyzed. The criteria and levels of social competence of students of pedagogical college are defined.